Hubungan Dukungan Keluarga Dengan Kepatuhan Minum Obat pada Penderita Kusta : Literature Review - Imam Ghazali; Yuly Peristiowati; Yenny Puspitasari (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
Leprosy infectious disease can cause peripheral nerve disorders and skin disorders. The problem in question is not only from a medical point of view but extends to the social, namely leprosy sufferers can be ostracized or shunned by society. So important is the role of the family in providing support for leprosy sufferers to achieve recovery through adherence to taking medication. The purpose of writing this literature review is to determine the relationship between family support and medication adherence in leprosy patients. The research design used a literature review conducted on a data base including Google Schoolar, PubMed, and Spinger. Article analysis found 16,776 but only 10 articles that met the inclusion criteria. The results of journal analysis showed that for each of the 10 articles, it was found that in 7 articles there was a relationship between family support and adherence to taking medication in leprosy patients. In addition, the other 4 articles said that the family plays an important role in providing support, encouragement, and motivation for family members who have leprosy to adhere to treatment. One of the factors that can increase treatment adherence in patients with chronic diseases is good family support.